2002
DOI: 10.1103/physreve.65.051923
|View full text |Cite
|
Sign up to set email alerts
|

Model for cardiorespiratory synchronization in humans

Abstract: Recent experimental studies suggest that there is evidence for a synchronization between human heartbeat and respiration. We develop a physiologically plausible model for this cardiorespiratory synchronization, and numerically show that the model can exhibit stable synchronization against given perturbations. In our model, in addition to the well-known influence of respiration on heartbeat, the influence of heartbeat (and hence blood pressure) on respiration is also important for cardiorespiratory synchronizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 19 publications
1
58
0
2
Order By: Relevance
“…The present simulation indicates that using the combined two methods we may have information on synchronization or desynchronization that may be induced in modulation and induced variability. It is also well known that human cardiovascular variables exhibit noisy dynamics [11] and the constructive role of noise component in particular in synchronization. We obtain that using the present method we may have information also on this modulating component.…”
Section: ( )mentioning
confidence: 99%
“…The present simulation indicates that using the combined two methods we may have information on synchronization or desynchronization that may be induced in modulation and induced variability. It is also well known that human cardiovascular variables exhibit noisy dynamics [11] and the constructive role of noise component in particular in synchronization. We obtain that using the present method we may have information also on this modulating component.…”
Section: ( )mentioning
confidence: 99%
“…They suggest that the model should be reparameterized to make all modeled variables physiologically plausible, and assume that this could lead to a "'unifying theory to account for slow oscillation' in cardiovascular variability". Kotani et al (2002) extended the model by noise and more detailed respiratory influences. They showed that the model can explain the synchronization between the heartbeat and the breathing frequency observed in humans (Kotani et al, 2002).…”
Section: Physiological Relevancementioning
confidence: 99%
“…Kotani et al (2002) extended the model by noise and more detailed respiratory influences. They showed that the model can explain the synchronization between the heartbeat and the breathing frequency observed in humans (Kotani et al, 2002). In a later study they also found that the (modified) SHM could produce statistically valid simulations of congestive heart failure and primary autonomic failure -diseases that are known to affect the parasympathetic and sympathetic neural activity (Kotani et al, 2005).…”
Section: Physiological Relevancementioning
confidence: 99%
“…Latter, Tolddo et al [8] found that synchronization was less abundant in normal subjects than in the transplant patients, which indicated that the physiological condition of the latter promotes cardiorespiratory synchronization. More recently, Kotani et al [14] developed a physiologically model to study the phenomena, and showed that both the influence of respiration on heartbeat and the influence of heartbeat on respiration are important for cardiorespiratory synchronization.…”
Section: Introductionmentioning
confidence: 99%
“…These systems can serve as a playground for the study of analysis techniques of nonlinear dynamics. Recently, the study of oscillations and couplings in these systems has gained increasing attention [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Among these, the nature of the couplings between human cardiovascular and respiratory systems has been widely studied [18][19][20][21][22][23][24][25][26], and is known to be both neurological [1] and mechanical [2].…”
Section: Introductionmentioning
confidence: 99%